2011
DOI: 10.5539/mas.v5n6p211
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Science Simulations, Guided-Discovery and Students’ Performance in Chemistry

Abstract: This study investigated the relative effectiveness of computer-based science simulations on students' achievement in chemistry at the secondary school level when compared with guided-discovery and the traditional expository teaching methods. The study used non-randomized pre-test -post-test control group design. The study sample was 89 Senior Secondary II (SSII) chemistry students drawn from Uyo Local Government Area, Akwa lbom State, Nigeria. Criterion sampling technique was used for sampling. Two hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…Some studies have indicated positive and significant effects in favor of computer simulation (Udo and Etiubon, 2011;Plass et al, 2012;Ezeudu and Okeke, 2013;Sentongo et al, 2013;Kotoka and Kriek, 2014;Okwuduba et al, 2018;Nnadi, 2019;Farkhanda and Muhammad, 2020;Jack et al, 2020;Adah, 2021).…”
Section: Computer Simulationmentioning
confidence: 99%
“…Some studies have indicated positive and significant effects in favor of computer simulation (Udo and Etiubon, 2011;Plass et al, 2012;Ezeudu and Okeke, 2013;Sentongo et al, 2013;Kotoka and Kriek, 2014;Okwuduba et al, 2018;Nnadi, 2019;Farkhanda and Muhammad, 2020;Jack et al, 2020;Adah, 2021).…”
Section: Computer Simulationmentioning
confidence: 99%
“…Obanyan ( 2010) maintain that science teachers should have the ability in creating suitable learning experiences during practical to mirror an environment for exploring self, solving problems, reasoning inductively and self-regulatory skills in order to provide lifelong learning. Furthermore, enhanced performance and retention of concepts can be gained by deliberate practice and engagement in active learning by means of guided-discovery (Udo & Etiubon, 2011;Koole et al, 2012). This comes with experience and confidence in carrying students along.…”
Section: B Teachers' Role and Practical Work Experiencementioning
confidence: 99%
“…Como estratégia de facilitar o ensino de Química em sala de aula, Udo (2011) propôs em simular a Ciência através de pacotes de software com alunos do secundário na Nigéria. Dois grupos de alunos foram analisados: o primeiro recebeu uma aula através do simulador e o outro uma aula tradicionalista (exposição oral tradicional).…”
Section: Ensino De Química E a Necessidade De Uma Abordagem Contextualizadaunclassified